Green bond issuance and corporate ESG performance: the perspective of internal attention and external supervision - Jinyu Chen; Yan Yang; Ran Liu; Yuan Geng; Xiaohang Ren (Humanities & Social Sciences Communications, 2023)
Abstract Based on the staggered difference-in-difference (DID) model, this paper uses Chinese listed firms between 2012 and 2020 to investigate the impact of green bond issuance on corporate environmental, social and governance (ESG) performance. We provide evidence that green bond issuance positively enhances corporate ESG performance. Green bond issuance mainly promotes corporate ESG performance through the internal attention effect and the external supervision effect. Moreover, the positive correlation between green bond issuance and corporate ESG performance is more prominent among companies with larger size, higher government subsidies and executives with environmental experience. The extended analysis shows that green bond issuance can promote the enhancement of firm valuation. This study provides theoretical guidance for the use of green financial systems to promote corporate ESG performance.